29P-D-7 Visual Analog Scaleによる情報スキルの主観評価と打鍵テスト評価との相関(主観評価,一般講演) - 松本, 有二; 宮本, 視典; 渡邉, 志 (バイオメディカル・ファジィ・システム学会大会講演論文集, 2011)
This paper discusses the correlation between information skills for students based on visual analog scale (VAS) and results of typing practice. The subjects are 12 college students. In order to investigate their typing skills, they practiced typing based on computer software named "TYPEQUICK". And in order to analyze their information skills, they asked to answer questionnaires on VAS. The experiment results shows that there exits a liner relationship between subjective evaluation of information skills based on VAS and results of typing practice.